Evaluation of Service Quality Provided by the Directorate General for Industrial Development (Al-Mansour Journal, 2022)
The issue of quality services has taken the lead in the interest of researchers in recent times for its impact on the economic sectors, especially the private industrial sector. The environment surrounding the current industrial organizations from the opening of markets and the intensification of competition so that the continuation of this sector to continue is impossible, must on governments help by supported and providing the services needed to improve the sector. As the general directorate for industrial development represents the governmental body that supports and supervises the progress and development of this sector by providing all the services it needs, it was necessary to evaluate the quality of services provided to industrial project owners so that they can cope with the current environment and its competition and the importer's entry to find out the most important obstacles facing them and work to remove them. On this basis, the research on the quality of service provided in the directorate-general for industrial development (DGDA) was examined by selecting a sample of 65 industrial entrepreneurs, and through the identification form used as a means of collecting information. Many statistical methods have been used to analyze respondents ' answers to achieve the desired results, and in light of the application of these methods has been reached many conclusions, as the study finally concluded with a set of recommendations based on the results achieved, the most notable being the need working to find ways to improve quality by shortening the time and maximizing the benefits of the services provided by the internet.
Keywords: Service Quality; Importance of Service quality; Dimension of Service Quality; Directorate General for Industrial Development